2020
DOI: 10.3233/jifs-189133
|View full text |Cite
|
Sign up to set email alerts
|

Violent activity recognition by E-textile sensors based on machine learning methods

Abstract: In the new era of technology with the development of wearable sensors, it is possible to collect data and analyze the same for recognition of different human activities. Activity recognition is used to monitor humans’ activity in various applications like assistance for an elderly and disabled person, Health care, physical activity monitoring, and also to identify a physical attack on a person etc. This paper presents the techniques of classifying the data from normal activity and violent attack on a victim. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For activity analysis, these frames were considered. For each frame type, a total of 8,000 to 10,000 data frames are reported and 1,500 sample frames are randomly chosen, consisting of one set of all acts [66][67] . Various pre-processing techniques are used to extract the meaningful data from the raw information such Principal component analysis (PCA), Multi-regression analysis (MRA) to ranked the highly correlated features as shown in Figure 4.…”
Section: Violent Motion (A6)mentioning
confidence: 99%
See 1 more Smart Citation
“…For activity analysis, these frames were considered. For each frame type, a total of 8,000 to 10,000 data frames are reported and 1,500 sample frames are randomly chosen, consisting of one set of all acts [66][67] . Various pre-processing techniques are used to extract the meaningful data from the raw information such Principal component analysis (PCA), Multi-regression analysis (MRA) to ranked the highly correlated features as shown in Figure 4.…”
Section: Violent Motion (A6)mentioning
confidence: 99%
“…Various pre-processing techniques are used to extract the meaningful data from the raw information such Principal component analysis (PCA), Multi-regression analysis (MRA) to ranked the highly correlated features as shown in Figure 4. After pre-processing, different supervised training techniques have been used in the dataset such as Naïve Bayes (NB), Support Vector Machine (SVM) , Decision Tree (DT), K-Nearest Neighbor (K-NN) in the controlled and uncontrolled environment [66][67].…”
Section: Violent Motion (A6)mentioning
confidence: 99%
“…In order to identify normal activity and brute force attack activity, Randhawa's team used decision tree, k-NN classifier, support vector machine and wearable inertial fabric sensor to conduct various experiments on machine learning (supervised) classification technology. The experimental results showed that the vector algorithm provided 97.6% accuracy and 0.85 seconds of computation time for activity classification [17]. To give feedback on the performance of body movements in physical activities, Ferreira et al proposed a validation system based on 2D human pose estimation networks and deep semantic features.…”
Section: Introductionmentioning
confidence: 99%